The Andean religious world view and the rite of the Capachocha - Martín Rubio, María Del Carmen (2009)
Following recent discoveries of offerings from small children age into snow-covered mountains of Peru, Chile and Argentina, decided to intensify the research on the motivations, behavioral patterns and ritual practices that accompanied this form human sacrifices to Andean deities. We base our studies on the release of a number of archaeologists and writers, especially Betanzos, who narrates in detail how these children were «buried alive by all the places where the Inca had a thousand children and four thousand girls and five years. « He describes «the girl Cachua Tanta», we give a detailed analysis «Ampato’s mummy ‘Juanita’,» «The mummies of Salta, the women and children companions in death, and finally identifies the survival of the ancestral worship of the Apus.